2006
DOI: 10.1148/rg.262055063
|View full text |Cite
|
Sign up to set email alerts
|

MR Pulse Sequences: What Every Radiologist Wants to Know but Is Afraid to Ask

Abstract: The use of magnetic resonance (MR) imaging is growing exponentially, in part because of the excellent anatomic and pathologic detail provided by the modality and because of recent technologic advances that have led to faster acquisition times. Radiology residents now are introduced in their 1st year of training to the MR pulse sequences routinely used in clinical imaging, including various spin-echo, gradient-echo, inversion-recovery, echo-planar imaging, and MR angiographic sequences. However, to make optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
173
0
24

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(198 citation statements)
references
References 29 publications
1
173
0
24
Order By: Relevance
“…If the wavelength of the RF field was different from that in human tissue, it would create constructive or destructive interference of the transmitted field, resulting in regional brightening or signal loss. 13 Thus, to achieve optimal calibration, the dielectric properties of polymer gels should mimic those of human tissue. The dielectric properties of the polymer gel samples were measured using a dielectric Win DETA 5.64 (Novocontrol Technologies) and a frequency range of 1.0 × 10 −2 to 3.0 × 10 5 Hz.…”
Section: Dielectric Properties: Permittivity and Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…If the wavelength of the RF field was different from that in human tissue, it would create constructive or destructive interference of the transmitted field, resulting in regional brightening or signal loss. 13 Thus, to achieve optimal calibration, the dielectric properties of polymer gels should mimic those of human tissue. The dielectric properties of the polymer gel samples were measured using a dielectric Win DETA 5.64 (Novocontrol Technologies) and a frequency range of 1.0 × 10 −2 to 3.0 × 10 5 Hz.…”
Section: Dielectric Properties: Permittivity and Conductivitymentioning
confidence: 99%
“…The dielectric properties of the polymer gel samples were measured using a dielectric Win DETA 5.64 (Novocontrol Technologies) and a frequency range of 1.0 × 10 −2 to 3.0 × 10 5 Hz. Normally, the dielectric test of human tissue is conducted using frequencies between 915 MHz and 2.45 GHz, 13 which is beyond the range of the machine. However, the results of the present test showed that the conductivity increased and the permittivity decreased with increasing frequency.…”
Section: Dielectric Properties: Permittivity and Conductivitymentioning
confidence: 99%
“…Magnetoencephalography or MEG measures electrical activity of the brain with similar principle to MRI , the Faraday's Law of induction (Bitar, et al 2006 …”
Section: Magneto Encephalography (Meg)mentioning
confidence: 99%
“…In spin echo (SE) sequences, the mis-mapping will occur in the frequency encoding direction, and show up as a bright band on one side and a dark band on the other side of a fat-soft tissue interface. In gradient refocused echo (GRE) sequences, the mis-mapping occurs in all directions, and is known as the ''india ink artifact'' [2]. Due to the absence of refocusing of field in-homogeneities, long TE GRE sequences are actually T2*-weighted rather than true T2-weighted sequences like that in the SE family.…”
mentioning
confidence: 99%
“…Due to the absence of refocusing of field in-homogeneities, long TE GRE sequences are actually T2*-weighted rather than true T2-weighted sequences like that in the SE family. The effects of chemical shift are hence, more prominent in GRE sequences, such as fast multi-planer spoiled gradient echo (FSPGR) and True FISP (fast imaging with steady-state precession), as a result in cycling of fat and water protons in and out of phase over time [2,3]. This persistent India ink artifact at the interface of abdominal fat with visceral structures results in a better visualization of the visceral outline [3].…”
mentioning
confidence: 99%